A survey of economic conditions in Africa, 1967 - United Nations (New York : United Nations, 1969)
This survey is an annual report on economic conditions in Africa. The basic time framework of the report is the period 1960-1966. Attempt was made to describe developments in the most recent year for which information is available.
"United Nations publication. Sales no.: E 68 . II . K . 4
.
rpm 21/04/2017
Loans
Keywords: Economic Conditions; Economic Conditions -- Africa; Gross Domestic Product; International Trade and Payment; Africa